THU0227 CAFFEINE INTAKE MODULATES DISEASE ACTIVITY AND CYTOKINES LEVELS IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS. (2nd June 2020) - Orefice, V.; Ceccarelli, F.; Barbati, C.; Lucchetti, R.; Olivieri, G.; Cipriano, E.; Natalucci, F.; Perricone, C.; Spinelli, F. R.; Alessandri, C.; Valesini, G.; Conti, F.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease mainly affecting women of childbearing age. The interplay between genetic and environmental factors may contribute to disease pathogenesis 1 . At today, no robust data are available about the possible contribute of diet in SLE. Caffeine, one of the most widely consumed products in the world, seems to interact with multiple components of the immune system by acting as a non-specific phosphodiesterase inhibitor 2 . In vitro dose-dependent treatment with caffeine seems to down-regulate mRNA levels of key inflammation-related genes and similarly reduce levels of different pro-inflammatory cytokines 3 . Objectives: We evaluated the impact of caffeine consumption on SLE-related disease phenotype and activity, in terms of clinimetric assessment and cytokines levels. Methods: We performed a cross-sectional study, enrolling consecutive patients and reporting their clinical and laboratory data. Disease activity was assessed by SLE Disease Activity Index 2000 (SLEDAI-2k) 4 . Caffeine intake was evaluated by a 7-day food frequency questionnaire, including all the main sources of caffeine. As previously reported, patients were divided in four groups according to the daily caffeine intake: <29.1 mg/day (group 1), 29.2-153.7 mg/day (group 2), 153.8-376.5 mg/day (group 3) and >376.6 mg/day (group 4) 5 . At the end of questionnaire filling, blood samples were collected from each patient to assess cytokines levels. These were assessed by using a panel by Bio-Plex assays to measure the levels of IL-6, IL-10, IL-17, IL-27, IFN-γ, IFN-α and Blys. Results: We enrolled 89 SLE patients (F/M 87/2, median age 46 years, IQR 14; median disease duration 144 months, IQR 150). The median intake of caffeine was 195 mg/day (IQR 160.5). At the time of the enrollment, 8 patients (8.9%) referred a caffeine intake < 29.1 mg/day (group 1), 27 patients (30.3%) between 29.2 and 153.7 mg/day (group 2), 45 patients (51%) between 153.8 and 376.5 mg/day (group 3) and 9 patients (10.1%) >376.6 mg/day (group 4). A negative correlation between the levels of caffeine and disease activity, evaluated with SLEDAI-2K, was observed (p=0.01, r=-0.26). By comparing the four groups, a significant higher prevalence of lupus nephritis, neuropsychiatric involvement, haematological manifestations, hypocomplementemia and anti-dsDNA positivity was observed in patients with less intake of caffeine (figure 1 A-E). Furthermore, patients with less intake of caffeine showed a significant more frequent use of glucocorticoids [group 4: 22.2%, versus group 1 (50.0%, p=0.0001), group 2 (55.5%, p=0.0001), group 3 (40.0%, p=0.009)]. Moving on cytokines analysis, a negative correlation between daily caffeine consumption and serum level of IFNγ was found (p=0.03, r=-0.2) (figure 2A ); furthermore, patients with more caffeine intake showed significant lower levels of IFNα (p=0.02, figure 2B ), IL-17 (p=0.01, figure 2C ) and IL-6 (p=0.003, figure 2D ). Conclusion: This is the first report demonstrating the impact of caffeine on SLE disease activity status, as demonstrated by the inverse correlation between its intake and both SLEDAI-2k values and cytokines levels. Moreover, in our cohort, patients with less caffeine consumption seems to have a more severe disease phenotype, especially in terms of renal and neuropsychiatric involvement. Our results seem to suggest a possible immunoregulatory dose-dependent effect of caffeine, through the modulation of serum cytokine levels, as already suggested by in vitro analysis. References: [1]Kaul et al Nat. Rev. Dis. Prim. 2016; 2. Aronsen et al Europ Joul of Pharm 2014; 3. Iris et al Clin Immun. 2018; 4. Gladman et al J Rheumatol. 2002; 5. Mikuls et al Arth Rheum 2002 Disclosure of Interests: Valeria Orefice: None declared, Fulvia Ceccarelli: None declared, cristiana barbati: None declared, Ramona Lucchetti: None declared, Giulio Olivieri: None declared, enrica cipriano: None declared, Francesco Natalucci: None declared, Carlo Perricone: None declared, Francesca Romana Spinelli Grant/research support from: Pfizer, Consultant of: Novartis, Gilead, Lilly, Sanofi, Celgene, Speakers bureau: Lilly, cristiano alessandri Grant/research support from: Pfizer, Guido Valesini: None declared, Fabrizio Conti Speakers bureau: BMS, Lilly, Abbvie, Pfizer, Sanofi